Traumatic acute stem rupture in stress shielding bone resorption of a bipolar radial head arthroplasty: case report and literature review - Cardile, Carlo; Arrigoni, Paolo; Cazzaniga, Carlo; Zaolino, Carlo; Ragni, Paolo; Randelli, Pietro Simone (Acta Biomedica Atenei Parmensis, 2021)
Bone resorption around the proximal portion of the stem of a radial head prosthesis is a frequent phenomenon. In the vast majority of cases it is not correlated with to be without clinical manifestations.  This radiographic sign, refers to the stress shielding effect has been more described in total hip replacement surgery. Few authors have noticed this phenomenon in radial head replacement. however, given the increasing number of these procedures, a careful surveillance is required in patients presenting this sign. We report a literature review and a case presentation of proximal stem rupture following a trauma in association to radiological periprosthetic bone resorption due to stress shielding and treated with revision surgery.